A new nasal mite of the genus Ptilonyssus (Rhinonyssidae) from Parus caeruleus (Passeriformes) from Russia - DIMOV, I. D. (Journal of the Hellenic Veterinary Medical Society, 2017)
A new species of nasal mite, Ptilonyssus mininovi wt sp> is described from the Azure Titmice Parus caeruteus Lt (Passeriformes: Paridae) from the Leningrad province, Russia, The new species and four previously known species, P, pinicoia Knee 2008, P. plesiotypicus Knee 2008, Pt pari Fain and Hyland 1963, and P. coccothraustis, Fain and Bafort 1963, are arranged here into a "pari" species complex with the genus Ptilonyssus.